Increased obstetric and neonatal risks in artificial cycles for frozen embryo transfers?. Issue 5 (May 2021) - Zaat, Tjitske R.; Brink, Anna J.; de Bruin, Jan-Peter; Goddijn, Mariëtte; Broekmans, Frank J.M.; Cohlen, Ben J.; Macklon, Nick S.; van Wely, Madelon; Groenewoud, Eva R.; Mol, Femke; ,
Abstract: Research question: What are the obstetric and neonatal risks for women conceiving via frozen–thawed embryo transfer (FET) during a modified natural cycle compared with an artificial cycle method. Design: A follow-up study to the ANTARCTICA randomized controlled trial (RCT) (NTR 1586) conducted in the Netherlands, which showed that modified natural cycle FET (NC-FET) was non-inferior to artificial cycle FET (AC-FET) in terms of live birth rates. The current study collected data on obstetric and neonatal outcomes of 98 women who had a singleton live birth. The main outcome was birthweight; additional outcomes included hypertensive disorder of pregnancy, premature birth, gestational diabetes, obstetric haemorrhage and neonatal outcomes including Apgar scores and admission to the neonatal ward or the neonatal intensive care unit and congenital anomalies. Results: Data from 82 out of 98 women were analysed according to the per protocol principle. There was no significant difference in the birthweights of children born between groups (mean difference –124 g [–363 g to 114 g]; P = 0.30). Women who conceived by modified NC-FET have a decreased risk of hypertensive disorders of pregnancy compared with AC-FET (relative risk 0.27; 95% CI 0.08–0.94; P = 0.031). Other outcomes, such as rates of premature birth, gestational diabetes or obstetric haemorrhage and neonatal outcomes, were not significantly different. Conclusions: The interpretation is that modified NC-FET is the preferred treatment in women with ovulatory cycles undergoing FET when the increased risk of obstetrical complications and potential neonatal complications in AC-FET are considered.